Mid-term outcomes of the R3™ delta ceramic acetabular system in total hip arthroplasty - Davis Edward T; Remes Ville; Virolainen Petri; Gebuhr Peter; Van Backle Bart; Revell Matthew P; Kopjar Branko (BMC, 2022)
BackgroundWhilst bony fixation of hip replacement has stable solutions, there remains controversy over which bearing best optimizes longevity and function. Ceramic-on-ceramic (CoC) bearing combinations are associated with lower risk of revision due to aseptic loosening and dislocation. Evidence for long-term functional outcomes of modern, 4th generation CoC bearings is limited. The aim of this study was to analyze outcomes and complications of the R3 (TM) Acetabular System (Smith & Nephew, Inc., Cordova, TN, USA) in combination with BIOLOX (R) Delta ceramic femoral head in patients undergoing primary total hip arthroplasty (THA).MethodsBetween June 2009 and May 2011, 175 patients (178 hips) were enrolled into a prospective, study at 6 sites in Europe and prospectively followed-up at 3 months and 1, 3, 5, and 7 years postoperative.ResultsTotal WOMAC score improved from 63 (range, 22-91) preoperative to 8 (range, 0-8) at 1-year follow-up and remained unchanged at 7-year follow-up. Modified Harris hip score improved from 45 (range, 10-87) preoperative to 83 (range, 25-100) at 3 months, 91 (range, 42-100) at 1 year, and 92 (range, 46, 100) at 7 years. UCLA Activity Rating Scale score improved from 3.3 (range, 1-8) preoperative to 6.2 (range, 2-8) at 1 year; it marginally declined to 5.8 (range, 3-8) at 7-year follow-up. There were 4 trochanteric fractures and 5 patients died of unrelated reasons. Three hips were revised (2 periprosthetic fractures and 1 subluxation). The 7-year cumulative survival rate was 98.3%.ConclusionClinical and functional improvements of THA with CoC bearing are maintained at 7 years postoperative.Trial registrationClinicalTrials.Gov, NCT03566082, Registered 10 January 2018-retrospectively registered,